# 14z + 96 = 28z - 100 z = ?

Feb 22, 2018

$z = - \frac{48}{43}$

#### Explanation:

Move all terms containing $z$ to one side and keep all other terms on another side:

$14 z - 14 z + 96 = 28 z - 14 z - 100 z$

$96 = 28 z - 14 z - 100 z$

(If we want to move $14 z$ from the left side to the right side, we'll need to subtract $14 z$ from each side.)

Now, simplify the side containing $z$'s by subtracting:

$96 = - 86 z$

Solve for $z$ . This means dividing each side by $- 86$, which would mean $- 86$ cancels out on the left side.

$\left(- \frac{96}{86}\right) = \left(\frac{\cancel{-} 86}{\cancel{-} 86}\right) z$

$z = \left(- \frac{96}{86}\right)$

Simplify:

$z = - \frac{48}{43}$

Feb 22, 2018

$z = 14$

#### Explanation:

Combine like terms on both sides.
$14 z + 96 = 28 z - 100$
$14 z - 14 z + 96 = 28 z - 14 z - 100$
$96 = 14 z - 100$
$96 + 100 = 14 z - 100 + 100$
$196 = 14 z$
Divide
$\frac{196}{14} = \frac{14 z}{14}$
$z = 14$

Feb 22, 2018

$z = 14$

#### Explanation:

We can start by adding 100 to both sides, and we get:

$14 z + 196 = 28 z$

We want to get the constant on one side and the variables on the other. So we can subtract $14 z$ from both sides, and we get:

$196 = 14 z$

Swapping the sides:

$14 z = 196$

We can divide both sides by $14$ to get:

$z = 14$